2021
DOI: 10.1111/iji.12553
|View full text |Cite
|
Sign up to set email alerts
|

Estimating HLA haplotype frequencies from homozygous individuals – A Technical Report

Abstract: We estimated HLA haplotype frequencies based on individuals homozygous for 4, 5 or 6 loci. Validation of our approach using a sample of over 3.4 million German individuals was successful. Compared to an expectation‐maximization algorithm, the errors were larger. However, our approach allows the unequivocal detection of rare haplotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Furthermore, we demonstrated that the H3K27M peptide vaccine induces an immune response across diverse HLA alleleotypes: the deconvoluted HLA restrictions of cognate CD4 + TCRs demonstrate restrictions to members of multiple class II HLA loci. DRB1*13:02 and DQB1*06:03 frequently co-occur on the same haplotype, whereas DRB1*07:01 and DQB1*06 are not a common haplotype pair 25 . Considering these allelic frequencies and the TCRs described in this work with their restrictions, 40-45% of the German population (where the INTERCEPT-H3 trial -NCT04808245 -is currently ongoing) could be covered with cell therapy using a pair of identified TCRs.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we demonstrated that the H3K27M peptide vaccine induces an immune response across diverse HLA alleleotypes: the deconvoluted HLA restrictions of cognate CD4 + TCRs demonstrate restrictions to members of multiple class II HLA loci. DRB1*13:02 and DQB1*06:03 frequently co-occur on the same haplotype, whereas DRB1*07:01 and DQB1*06 are not a common haplotype pair 25 . Considering these allelic frequencies and the TCRs described in this work with their restrictions, 40-45% of the German population (where the INTERCEPT-H3 trial -NCT04808245 -is currently ongoing) could be covered with cell therapy using a pair of identified TCRs.…”
Section: Discussionmentioning
confidence: 94%
“…For alleles DRB1*04:07g and DRB1*16:02g, both of which are present in virtually all Native populations from North, Central and South America, but also in Europe (DRB1*04:07g) and Asia (DRB1*16:02g), the examination of the DQB1 associations is distinctive. DRB1*04:07~DQB1*03:02 is a conserved Native American haplotype block while DRB1*04:07~DQB1*03:01 is found in Europeans ( 65 , 67 ). Similarly, DRB1*16:02~DQB1*03:01 is found in Native Americans while DRB1*16:02~DQB1*05:02 is typically seen in Asians and Africans ( 61 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we demonstrated that the H3K27M peptide vaccine induces an immune response across diverse HLA alleleotypes: The deconvoluted HLA restrictions of cognate CD4 + TCRs demonstrate restrictions to members of multiple class II HLA loci. DRB1*13:02 and DQB1*06:03 frequently co-occur on the same haplotype, whereas DRB1*07:01 and DQB1*06 are not a common haplotype pair ( 29 ). Considering these allelic frequencies and the TCRs described in this work with their restrictions, 40 to 45% of the German population (where the INTERCEPT-H3 trial, NCT04808245, is currently ongoing) could be covered with cell therapy using a pair of identified TCRs.…”
Section: Discussionmentioning
confidence: 99%